Penerimaan dan Penggunaan Teknologi Generative AI dalam Pembelajaran di Sekolah Menengah Atas Menggunakan TAM - Agra Tiadef; Daniel Arsa; Miranty Yudistira (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the acceptance and use of Generative AI technology in learning activities at Senior high school 3 Sungai Penuh City using the Technology Acceptance Model (TAM) approach. The development of Artificial Intelligence provides opportunities to improve the effectiveness, personalization, and quality of learning. However, the implementation of this technology at the secondary education level still faces challenges such as low digital literacy, limited user readiness, and the lack of research related to the impact of Generative AI on students’ academic achievement. Preliminary research results indicate that most students and teachers are familiar with and have used services such as ChatGPT, Gemini, and Perplexity AI in learning activities. This study employs a quantitative method using the Structural Equation Modeling–Partial Least Square (SEM-PLS) approach. The variables analyzed include Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), Behavioral Intention (BI), Actual Use (AU), and Student Grades. Data were collected through questionnaires distributed to students as respondents. The results are expected to show that perceived ease of use and perceived usefulness positively influence attitudes, behavioral intentions, and the actual use of Generative AI, which in turn impacts students’ academic achievement. This study is expected to provide both theoretical and practical contributions to the development of Generative AI utilization in secondary education.